A Comparative Meta-analysis of the Effects of Gamification and Flipped Classroom on Secondary School Students’ Mathematics Achievement - Vega, Amelia; Hidayanto, Erry; Muksar, Makbul (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2026)
This study compares the effectiveness of gamification and the flipped classroom on secondary school students’ mathematics achievement through a systematic review and meta-analysis. The synthesis follows PRISMA 2020 and includes 16 quasi-experimental studies published between 2015 and 2025, comprising 5 gamification studies and 11 flipped classroom studies. Effect sizes were calculated using Hedges’ g and pooled using a random-effects model with the Hartung-Knapp-Sidik-Jonkman (HKSJ) adjustment to accommodate heterogeneity. The results show that gamification has a small-to-moderate positive point estimate (g = 0.437), but the confidence interval crosses zero under high heterogeneity (I² ≈ 87%), indicating that the evidence for benefit is uncertain. The flipped classroom shows a moderate-to-large pooled effect (g = 1.009) with a significant confidence interval, although heterogeneity is also high (I² ≈ 86%). Subgroup analysis found a significant difference between the two approaches, but meta-regression indicates that model type is not a significant predictor after between-study variation is accounted for. Overall, the findings suggest that effectiveness is design-sensitive and influenced more by implementation quality and context than by the instructional label alone.